Content Marketing in the Digital Age: Creating Engaging and Shareable Content that Captures Audience Attention - Ernestivita, Gesty; Suhendra, Euphrasia Suzy; Stratan, Alexandru (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Content marketing has become key in the competitive digital marketing landscape, where visual elements play an important role in attracting attention and increasing audience engagement. This research aims to analyze the influence of visual elements in content marketing on audience engagement and content sharing levels. Using the PRISMA method, articles from international databases were screened to obtain relevant and valid data. The research results show that high-quality visual elements significantly increase audience engagement and motivate content sharing. The implications of this research underscore the importance of investing in quality visual content and leveraging analytics for more effective marketing strategies.